Cystic fibrosis: candidate selection and impact of the cystic fibrosis transmembrane conductance regulator therapy. Issue 3 (June 2022) - Lehr, Carli J.; Pilewski, Joseph M.
Abstract : Purpose of review: Over the past decade, the development of highly effective cystic fibrosis (CF) transmembrane conductance regulator (CFTR) modulators has dramatically ameliorated the manifestations of CF for most patients. Perhaps most importantly, CFTR modulators impact the development and progression of advanced lung disease (ALD) and are changing the CF population accessing lung transplant. Recent findings: A recent phase 3 trial of elexacaftor/tezacaftor/ivacaftor (ETI) demonstrated efficacy for individuals with at least one copy of the most common CF mutation, F508del. Studies of CFTR modulator therapy in patients with ALD have demonstrated similar improvements in lung function, nutrition, and pulmonary exacerbation frequency as seen in individuals with higher lung function. Due to improvements with ETI, rates of lung transplant for CF have declined and individuals are achieving stability in lung function. Nevertheless, the Cystic Fibrosis Foundation guidelines for lung transplant referral should be used to guide referral decisions for all individuals with CF, including those on CFTR modulator therapy, to allow remediation of modifiable barriers to transplant. ETI may be used in the posttransplant setting but for selected individuals and with close monitoring. Summary: Increasing access to highly effective CFTR modulators has changed the trajectory of lung disease in CF for many, but not all, individuals and there remain individuals who cannot access therapy or whose mutations do not respond to modulators. Lung transplant remains an important treatment option for individuals with advanced CF lung disease. Increasing attention will be required to optimize decisions of when to list for transplant.